1992
DOI: 10.1128/aac.36.9.2037
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of penciclovir and acyclovir against herpes simplex virus types 1 and 2

Abstract: Penciclovir (PCV) and acyclovir are acyclic guanine analogs which inhibit herpes simplex virus (HSV) DNA polymerase. Their 50% infective doses were 0.5 to 0.8 ,ug/ml for clinical isolates of HSV-1 and 1.3 to 2.2 ,ug/ml for HSV-2. Furthermore, HSV-infected cultures receiving 2-h pulses of PCV had 2-to 50-fold less HSV than acyclovir-treated cultures, consistent with the prolonged intracellular half-life of PCV triphosphate.Penciclovir [PCV; 9-(4-hydroxy-3-hydroxymethylbut-1-yl) guanine] is an acyclic guanine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 5 publications
7
27
0
Order By: Relevance
“…In previous work with HSV-1 and HSV-2, penciclovir caused prolonged inhibition of viral replication (Boyd et al, 1987;Vere Hodge and Perkins, 1989;Earnshaw et al, 1992;Bacon and Schinazi, 1993). In addition, repeated daily pulse treatment of HSV-infected cells has demonstrated that penciclovir has more prolonged antiviral activity than aciclovir (Weinberg et al, 1992). In the present studies, pulse treatment of VZV-infected cultures with penciclovir reduced VZV DNA synthesis significantly more effectively than for aciclovir (Table 3).…”
Section: Inhibition Of Varicella-zoster Virus By Penciclovir 75supporting
confidence: 49%
“…In previous work with HSV-1 and HSV-2, penciclovir caused prolonged inhibition of viral replication (Boyd et al, 1987;Vere Hodge and Perkins, 1989;Earnshaw et al, 1992;Bacon and Schinazi, 1993). In addition, repeated daily pulse treatment of HSV-infected cells has demonstrated that penciclovir has more prolonged antiviral activity than aciclovir (Weinberg et al, 1992). In the present studies, pulse treatment of VZV-infected cultures with penciclovir reduced VZV DNA synthesis significantly more effectively than for aciclovir (Table 3).…”
Section: Inhibition Of Varicella-zoster Virus By Penciclovir 75supporting
confidence: 49%
“…In agreement with previous work (Weinberg et al, 1992;Bacon and Schinazi, 1993;Bacon et al, 1996b), penciclovir limited the replication of HSV-1 and HSV-2 in human embryonic lung fibroblasts, in cultures infected at 0.01 pfu celr ' and treated continuously for 72 h, more effectively than aciclovir (p = 0.0001; n = 6 strains; Table 1). In the present study, AUCs for the dose response curves were compared, the advantage being that all the data are included in the analysis rather than comparing the compounds at individual concentrations (Weinberg et al, 1992;Bacon et al, 1996b).…”
Section: Discussionsupporting
confidence: 79%
“…Subsequently it was reported that penciclovir reduced virus replication more effectively than aciclovir following treatment of human embryonic lung cells infected at low multiplicity (0.01 pfu cell-i) for 72 h (Weinberg et al, 1992). This study was confirmed and extended in experiments with several strains of HSV-1 and HSV-2 (Bacon and Schinazi, 1993;Bacon et al, 1996b).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations